2,6-Dioxabicyclo[3.3.1]nonan-3-ones: from natural product treasure troves to synthetic triumphs - Choudhury, Utkal Mani; Das, Pragna Pratic; Mohapatra, Debendra Kumar (RSC Advances, 2026)
2,6-Dioxabicyclo[3.3.1]nonan-3-ones represent a structurally captivating and biologically potent class of natural products. This review comprehensively chronicles the discovery, isolation, and synthetic evolution of 2,6-disubstituted THP containing diverse bridged bicyclic lactone derivatives. Spanning over three decades of research, we present a chronological survey of naturally occurring THP-fused lactones highlighting their origins, structural diversity, and the synthetic ingenuity employed to construct these challenging frameworks. Emphasis is placed on oxa-Michael addition, tandem isomerization followed by C-O and C-C bond forming reaction, Prins reactions, and ring-closing metathesis each offering unique strategic advantages. Particular attention is paid to the stereochemical complexity and regioselectivity challenges inherent in assembling the densely functionalized polyol systems of these compounds. The purpose of this review is to offer a comprehensive introduction for those new to the field, while also spotlighting the latest exciting advancements in the field.